2001
DOI: 10.1007/s11661-001-0265-9
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen thermal desorption relevant to delayed-fracture susceptibility of high-strength steels

Abstract: The susceptibility to hydrogen embrittlement (HE) of martensitic steels has been examined by means of a delayed-fracture test and hydrogen thermal desorption analysis. The intensity of a desorptionrate peak around 50 ЊC to 200 ЊC increased when the specimen was preloaded and more remarkably so when it was loaded under the presence of hydrogen. The increment appeared initially at the lowtemperature region in the original peak. As hydrogen entry proceeded, the increment then appeared at the high-temperature regi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

8
165
0
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 319 publications
(174 citation statements)
references
References 66 publications
8
165
0
1
Order By: Relevance
“…One is that, in most studies, the hydrogen content of specimens was not identified. Only about ten references (for example, References 6,7,15,and 20) of the more than several hundred articles recently surveyed by the authors include data on the measurement of hydrogen content.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One is that, in most studies, the hydrogen content of specimens was not identified. Only about ten references (for example, References 6,7,15,and 20) of the more than several hundred articles recently surveyed by the authors include data on the measurement of hydrogen content.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] The present authors have investigated microscopically the effect of hydrogen on fatigue crack growth behavior, including the measurement of the exact hydrogen content, in various materials such as low-carbon, Cr-Mo, and stainless steels. For example, particularly important phenomena found by the authors' fatigue studies (Murakami et al, [32,33] Uyama et al, [34,35] Kanezaki et al, [36] and Tanaka et al [37] ) are the localization of fatigue slip bands, strain-induced martensitic transformation in types 304, 316, and even 316L, and also strong frequency effects on fatigue crack growth rates.…”
Section: Introductionmentioning
confidence: 99%
“…DOI: 10.1103/PhysRevLett.103.085501 PACS numbers: 61.72.JÀ, 61.72.SÀ, 71.15.Mb, 71.15.Nc In the past few decades, a variety of fundamentally new phenomena has been observed in metals and their alloys under hydrogen-rich conditions, such as large volume contractions in body-centered cubic (bcc) -Fe [1,2], and the enhancement of diffusion at metal-metal junctions [3]. Furthermore, the well-known problem of hydrogeninduced degradation of the mechanical properties of metals has had significant impact in Fe-rich alloys such as hardened steels that suffer severe embrittlement [4,5]. Experimental and theoretical evidence [1][2][3][4][5][6][7] suggests that one unifying theme behind these hydrogen-mediated effects is the strong interaction between hydrogen impurities and other point defects in the material, and the subsequent microstructural changes that occur as a result of that interaction.…”
mentioning
confidence: 99%
“…Furthermore, the well-known problem of hydrogeninduced degradation of the mechanical properties of metals has had significant impact in Fe-rich alloys such as hardened steels that suffer severe embrittlement [4,5]. Experimental and theoretical evidence [1][2][3][4][5][6][7] suggests that one unifying theme behind these hydrogen-mediated effects is the strong interaction between hydrogen impurities and other point defects in the material, and the subsequent microstructural changes that occur as a result of that interaction. Although a rich experimental literature detailing macroscopic effects exists, fundamental understanding of the interactions of hydrogen with point defect clusters (PDCs) in metals is limited.…”
mentioning
confidence: 99%
“…The mechanism of hydrogen diffusion through wear-induced nascent surfaces is supported by researchers who have found hydrogen to have diffused during RCF testing [5,9,[11][12][13] with measured concentrations of between 0.1 and 4.2 ppm [5,9,11], the concentration of hydrogen measured also being proportional to the wear on the steel during sliding tests [9].…”
Section: Introductionmentioning
confidence: 85%